Information literacy importance and consequences - Henninger, Maureen
The brief for this lecture in honour of Prof. Gabriel A. Bernardo, the doyen of Philippine librarianship, was twofold - to explore what promotes informed societies and responsible citizenry, and to examine the supposition that there is a role for libraries in a democratic society. The paper takes the position that such an endeavour in the digital age must extend to all information professionals and informed individuals, since librarians are part of the information profession, and each is an individual, a citizen, an educator, and an information practitioner. It also proposes that discussion about informed societies and responsible citizenry is based on the proposition that societies and individuals have agency, that they can and do make informed decisions concerning governments and governance, that they must be informationally literate, a concept that includes the many literacies that emerge and overlap in the current, dynamic information environment. The paper raises important issues of trust, ethics, allegations and responsibilities concerning the technology giants, in particularly search engines and social media. The intention of this paper was not to be partisan in these issues and debates, or to provide answers. Rather it was to persuade the readers that media and digital literacy mandate an awareness of these issues. Importantly, it was my objective to argue that not being literate in these matters has dire consequences for informed societies and responsible citizenry; and to argue that information professionals, in all their roles, have a critical part to play in this endeavour.
Keywords: Information literacy